Solvent effect on the NO2 sensing properties of multi-walled carbon nanotubes - Nikita I. Lapekin; Tatyana V. Anufrieva; Arina V. Ukhina; Artem A. Shestakov; Alexander G. Bannov (Chimica Techno Acta)
This article is devoted to the investigation of the influence of the solvent on sensing properties, such as response and recovery rate, of chemiresistive gas sensors. Multi-walled carbon nanotubes were used as an active material for the sensors. The initial material was investigated by scanning electron spectroscopy and transmission electron microscopy, low-temperature nitrogen adsorption, Raman spectroscopy, and X-ray diffraction. The active material was produced by drop casting. Different polar solvents (acetone and ethanol) were used for suspension preparation. Textolite with copper contacts on the edges of one side was used as a sensor substrate. The gas sensing properties (the response and the recovery time) were investigated in the range of 100–500 ppm NO2 at room temperature. The films made using different solvent suspensions showed high sensitivity and rapid recovery rate to nitrogen dioxide. It was found that the method of film preparation has an effect on the measured sensing properties. The films prepared using different suspensions possessed different properties: the film made from the acetone suspension had the response values from 8.49% to 20.26%, and the recovery values from 0.06%/min to 0.16%/min. The response of the film made from the ethanol suspension increased , being from 12.25% to 23.63%; the recovery rate were also increased (from 0.19%/min to 0.39%/min).